Infective Native Aneurysms of the Femoropopliteal Arteries : A Systematic Review and Pooled Analysis - Smet, Nick; Bérard, Xavier; Ljungquist, Oskar; van den Hoven, Pim; Sörelius, Karl (Journal of Vascular Surgery, 2025)
OBJECTIVE: Infective native aneurysms of the femoropopliteal arteries (INA-FPs) are rare and mostly reported in intravenous drug users (IVDU). This study aimed to summarize all cases of INA-FPs presented in the literature, to describe patient characteristics, microbiology, treatments and outcomes, and compare IVDU with non-IVDU patients. METHODS: A systematic search of PubMed, ScienceDirect, Embase and the Cochrane Library was done for studies published between 1990 and July 2024. The study followed PRISMA guidelines and articles were scrutinized regarding patient characteristics, anatomical segment, etiology, microbiology, treatment modalities and outcomes. RESULTS: Eighty-two studies comprising 368 patients with 382 INA-FPs were included. INA-FPs were located in the common femoral artery (CFA) in 305 cases (79.8%), the deep femoral artery in 4 (1.0%), the superficial femoral artery in 45 (11.8%), and the popliteal artery in 28 (7.3%). These INA-FPs developed in 299 IVDU (81.3%) and in 69 non-IVDU patients (18.7%). IVDU patients were younger (mean age 39 vs. 65 years, p < .001), more frequently had CFA involvement (93.2% vs. 23.3%, p < .001), and had lower 1-year mortality rates (2.9% vs. 17.3%, p < .001). The most common pathogen was Staphylococcus aureus (39%). Details on multi-disciplinary team management and antimicrobial therapy was missing. Ligation was the most performed treatment for IVDU patients (89.3%), whereas bypass was the most used for non-IVDU (69.6%). In the entire cohort, bypass was associated with a 5-fold increase in rebleeding risk compared with ligation, p < .001, and 50% were fatal. Ligation demonstrated a 4-fold increased risk of claudication compared with bypass, 24% vs 6%, but amputation rates were equal. CONCLUSION: INA-FPs are rarely reported, with significant differences in patient characteristics, surgical management and outcome between IVDU and non-IVDU patients. These findings underscore the need for tailored multi-disciplinary team management that carefully balances the benefits of revascularization against the risks of fatal bleeding.
Copyright © 2025. Published by Elsevier Inc.